Surgery for intraductal papillary mucinous neoplasms in young patients: high-risk population - Kaiser, Jörg; Hackert, Thilo; Hinz, Ulf; Mayer, Philipp; Tjaden, Christin; Roth, Susanne; Pausch, Thomas; Heger, Ulrike; Heckler, Max; Saeedi, Mohammed al; Büchler, Markus W.; Loos, Martin (Surgery, 2023)
BACKGROUND: Intraductal papillary mucinous neoplasms of the pancreas are uncommon in young individuals. Management of these patients is challenging because the risk of malignancy and recurrence after surgery remains unclear. The aim of the present study was to assess the long-term risk for intraductal papillary mucinous neoplasm recurrence after surgery for intraductal papillary mucinous neoplasms in patients ≤50 years of age. METHODS: Perioperative and long-term follow-up data of patients who had undergone surgery for intraductal papillary mucinous neoplasms between 2004 and 2020 were extracted from a prospective unicentric database and retrospectively analyzed. RESULTS: Seventy-eight patients underwent surgical treatment for benign intraductal papillary mucinous neoplasms (low-grade n = 22 and intermediate-grade n = 21) and malignant intraductal papillary mucinous neoplasms (high-grade n = 16 and intraductal papillary mucinous neoplasm-associated carcinoma n = 19). Severe postoperative morbidity (Clavien-Dindo ≥III) was found in 14 patients (18%). The median length of hospital stay was 10 days. No perioperative mortality was observed. The median length of follow-up was 72 months. Recurrence of intraductal papillary mucinous neoplasm-associated carcinoma was found in 6 patients (19%) with malignant intraductal papillary mucinous neoplasm and 1 patient (3%) with benign intraductal papillary mucinous neoplasm. CONCLUSION: Surgery for intraductal papillary mucinous neoplasm is safe and can be performed with low morbidity and potentially no mortality in young patients. Given the high rate of malignancy (45%), these patients with intraductal papillary mucinous neoplasms represent a high-risk population, and prophylactic surgical treatment should be considered in these patients with long life expectancies. Regular clinical and radiologic follow-up examinations are important to rule out disease recurrence, which is high, especially in patients with intraductal papillary mucinous neoplasm-associated carcinoma.
Gesehen am 12.09.2023